2014
DOI: 10.5326/jaaha-ms-5968
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Intravesicular Ureteroneocystostomy Techniques to Correct Ureteral Ectopia in a Male Cat

Abstract: A 2 yr old castrated male Himalayan presented for evaluation and treatment of persistent urinary incontinence that had been present since birth. Ultrasonographic evaluation of the urinary tract revealed suspected bilateral, extramural, ureteral ectopia that was confirmed at the time of surgical exploration. Marked left hydroureter and a normal right ureter were found entering the urethra ∼ 2 cm caudal to the bladder neck. An intravesicular mucosal apposition (modified Leadbetter-Politano) and "drop-in" uretero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Congenital abnormalities accounted for only 18% of our series of incontinent cats and included 4 cats with congenital spinal canal malformations (eg, Manx syndrome or spinal dysraphism), 1 cat with bilateral ureteral ectopia, 2 cats with presumed congenital USMI, and 1 cat with urethral hypoplasia . These and other congenital causes of UI in cats have been reported previously .…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Congenital abnormalities accounted for only 18% of our series of incontinent cats and included 4 cats with congenital spinal canal malformations (eg, Manx syndrome or spinal dysraphism), 1 cat with bilateral ureteral ectopia, 2 cats with presumed congenital USMI, and 1 cat with urethral hypoplasia . These and other congenital causes of UI in cats have been reported previously .…”
Section: Discussionmentioning
confidence: 73%
“…In our series of cats, UI was associated with a variety of congenital and acquired disorders that affected both phases of micturition with similar frequency. The proportional morbidity of causes, sex, age distribution, and outcomes of UI in our series of cats differed substantially from previous reports of UI in cats and dogs . Our observations indicated that spinal cord disorders were a common cause of UI in cats and were associated with less favorable outcomes compared to bladder and urethral disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex predisposition has also been reported in dogs, where females are 20 times more likely to develop ureteral ectopia than males 11,12,23 . In canine patients, the anatomy of the male urethra plays a role.…”
Section: Discussionmentioning
confidence: 94%
“…There are limited case reports in cats with unilateral or bilateral extramural ectopia. [9][10][11][12][13][14][15][16] Double ureters and ureteral ectopia in a single cat study, and ectopic ureterocele in another cat study have been also reported in past. 12,17 The literature search did not reveal studies describing confirmed unilateral extramural ectopia in a cat with combined CT and US findings.…”
Section: Discussionmentioning
confidence: 99%